Proceedings of the 2019 ACM Conference on International Computing Education Research 2019
DOI: 10.1145/3291279.3339417
|View full text |Cite
|
Sign up to set email alerts
|

Admitting Students through an Open Online Course in Programming

Abstract: Since 2012, part of computer science student body at the University of Helsinki has been selected by using a massively open online version of the same introductory programming course that our freshmen take. In this multi-year study, we compare study success between students accepted through the online course (MOOC intake) and students accepted through the traditional entrance exam and high school matriculation exam based intake (normal intake). Our findings indicate that the MOOC intake perform better in compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…As a result, the program did not appear to open new pathways for people from under-represented groups in supply chain management. Other studies of blended programs have also found that the programs tend to have fewer students from underrepresented groups (Leinonen et al, 2019) and benefit already high-achieving students (Asarta & Schmidt, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…As a result, the program did not appear to open new pathways for people from under-represented groups in supply chain management. Other studies of blended programs have also found that the programs tend to have fewer students from underrepresented groups (Leinonen et al, 2019) and benefit already high-achieving students (Asarta & Schmidt, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Most of the students enter the computer science programme through what we call the "main intake", which consists of two possible intake routes: an entrance exam or high school matriculation examination grades. The computer science programme also used to have a third intake route for the main intake, a MOOC intake described in [11,20], and similar to [13]. The MOOC intake has since been discontinued, but is included in the data set for the sake of comparison.…”
Section: Methodology 31 Contextmentioning
confidence: 99%
“…This is the largest group in the data, and the students from this intake usually have very few, if any, courses completed at the time of the admission. In the years under study, the university also had a MOOC intake, which allows students to complete a semester long programming MOOC and apply for the university if they succeed well enough [11,20]. These students have at least 10 credits from the programming MOOC.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that there is no difference in gender in completion rates of MOOCs in general [20], but STEM subjects may suffer from a lower retention rate for women [33]. Similarly, a recent study suggested that using a MOOC in programming for recruiting students into CS, while yielding students who perform better in their CS studies, may also lead to increased gender disparity [24].…”
mentioning
confidence: 99%